2004
DOI: 10.2975/27.2004.235.242
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral group therapy for insomnia in individuals with serious mental illnesses: A preliminary evaluation.

Abstract: Chronic insomnia is a problem among individuals with serious mental illnesses. In an effort to expand treatment options, we examined whether well-established cognitive-behavioral treatments for insomnia developed for individuals in the general population generalize to those for people with serious mental illnesses. Individuals participated in comprehensive sleep evaluations and cognitive-behavioral therapy. Results suggest that sleep problems often began during periods of distress and/or exacerbation of illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
11
0
1
Order By: Relevance
“…They stressed the need to attend to the symptoms and experiences of people with psychotic disorders when administering CBT-I. Both studies simplified intervention materials and explanations; Dopke and colleagues additionally allowed for repetition in presentation and taught people how to adjust CBT-I skills to their symptom levels and medication side effects [47]. They noted comprehension difficulties for some participants suggesting the need for more accommodation to cognitive deficits and cited a need to build in more practice and motivational enhancement to help clients use behavioral strategies consistently.…”
Section: Treatment and Managementmentioning
confidence: 96%
See 1 more Smart Citation
“…They stressed the need to attend to the symptoms and experiences of people with psychotic disorders when administering CBT-I. Both studies simplified intervention materials and explanations; Dopke and colleagues additionally allowed for repetition in presentation and taught people how to adjust CBT-I skills to their symptom levels and medication side effects [47]. They noted comprehension difficulties for some participants suggesting the need for more accommodation to cognitive deficits and cited a need to build in more practice and motivational enhancement to help clients use behavioral strategies consistently.…”
Section: Treatment and Managementmentioning
confidence: 96%
“…Two thirds (n= 12) showed a clinically significant change in self-reported insomnia symptoms; half of these (n=6) maintained 50 % improvement over 1 month. Dopke and colleagues enrolled 11 people with mental health disorders (including three with schizophrenia spectrum) and provided 10 CBT-I group sessions, resulting in significant improvements in self-reported sleep satisfaction, interference of sleep on daily functioning, sleep concerns, and number of skills used (e.g., positive sleep habits such as stimulus control) [47]. However, sleep diaries did not show significant changes in sleep parameters, an unexpected finding given their significant change in CBT-I trials with other populations [47] and their importance as a standard outcome measure in CBT-I trials [48].…”
Section: Treatment and Managementmentioning
confidence: 98%
“…15 Other case series or quasi-experimental studies have suggested CBT may be efficacious for treating insomnia in such specific patient groups as those with chronic pain, 16 cancer, 17 posttraumatic stress disorder, 18 and clinical depression 19 and those with mixed serious mental disorders. 20 In addition, a number of small to moderately sized, single-site, randomized clinical trials have suggested that CBT is efficacious for patients with insomnia and comorbid chronic peripheral pain syndromes, 21 treated breast cancer, 22 fibromyalgia 23 , mixed medical disorders, 24 mixed psychiatric and medical disorders, 25 and alcoholism. 26 Despite these findings, it is yet to be determined whether patients with PI or CMI show similar improvement from an equal and standard "dose" of CBT intervention.…”
mentioning
confidence: 99%
“…However, few people with SMI access treatment for insomnia (Klingaman, McCarthy, Schwartz, Gehrman, & Bennett, ; Qaseem, Kansagara, Forciea, Cooke, & Denberg, ). When they do, they have more difficulty adhering (Dopke, Lehner, & Wells, ; Siebern & Manber, ), experience more modest gains (Jansson‐Fröjmark & Norell‐Clarke, ; Harvey et al., ), and are less likely to retain gains long‐term (Harvey et al., ) compared with people without SMI. Experts have called for close examination of beliefs about insomnia among people with SMI as possible obstacles to treatment adherence and response (Faulkner & Bee, ; Freeman et al., ; Siebern & Manber, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, few people with SMI access treatment for insomnia (Klingaman, McCarthy, Schwartz, Gehrman, & Bennett, 2017;Qaseem, Kansagara, Forciea, Cooke, & Denberg, 2016). When they do, they have more difficulty adhering (Dopke, Lehner, & Wells, 2004;Siebern & Manber, 2011), experience more modest gains (Jansson-Fröjmark & Norell-Clarke, 2016;Harvey et al, 2015), and are less likely to retain gains longterm (Harvey et al, 2015) compared with people without SMI.…”
Section: Introductionmentioning
confidence: 99%